2020
DOI: 10.1111/ene.14176
|View full text |Cite
|
Sign up to set email alerts
|

A prospective case series of sphenopalatine ganglion pulsed radiofrequency therapy for refractory chronic cluster headache

Abstract: Background and purpose: The management options for chronic cluster headache (CCH) are limited and a significant proportion of patients become refractory to pharmacological treatments. Pulsed radiofrequency (PRF) of the sphenopalatine ganglion (SPG) may present an efficacious, minimally invasive treatment modality for patients with refractory CCH. We describe the clinical outcomes of 14 patients with refractory CCH treated with PRF of the SPG. Methods: Patients with medically refractory CCH who underwent percut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…A study with chronic refractory cluster headache reported a transient increase in pain intensity in 36% of treated patients. However, the method applied in this study was percutaneous, and other reported side effects were more closely related to the nature of the approach taken [32] . Another study on radicular pain also reported a temporary increase in pain intensity following treatment that lasted less than a day without any major side effects [33] .…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…A study with chronic refractory cluster headache reported a transient increase in pain intensity in 36% of treated patients. However, the method applied in this study was percutaneous, and other reported side effects were more closely related to the nature of the approach taken [32] . Another study on radicular pain also reported a temporary increase in pain intensity following treatment that lasted less than a day without any major side effects [33] .…”
Section: Discussionmentioning
confidence: 78%
“…However, the method applied in this study was percutaneous, and other reported side effects were more closely related to the nature of the approach taken. [32] Another study on radicular pain also reported a increase in pain intensity following treatment that lasted less than a day without any major side effects. [33] The participants of our study also did not report any major side effects due to treatment, and less than 2% reported discomfort with the intervention, with no statistically significant difference between the groups.…”
Section: Discussionmentioning
confidence: 98%
“…At the same time, the electrode tip temperature was maintained at 42℃without disrupting motor nerve function. Mild temperature energy of PRF therapy did not cause nerve damage and would not produce long-term clinical effects [24], Moor et al performs SG pulsed radiofrequency to treat cluster headaches (n = 2) and shows that 50%, 22%, and 28% have complete, marked/partial, and no improvement, respectively; through 12 months of follow-up, these reduced to 28%, 37%, and 37%, respectively [25]. In our study, we observed that the signi cant and total effective rates at 1-week post-procedure were 67.86% and 89.29%, and as time went on, the signi cant and total effective rates at 24 weeks post-procedure were 17.86% and 32.14%.…”
Section: Discussionmentioning
confidence: 99%
“… 8 Kim ED and Kim K have revealed that pulsed radiofrequency treatment of dorsal root ganglion in managing herpes zoster neuralgia has achieved ideal therapeutic effects, 9 , 10 and nerve block with steroid injection can also reduce all types of neuralgia. 11 , 12 It is worth mentioning that when herpes zoster is involved in the neck and upper limb, especially in the area of C3-C8, the adjacent vertebral artery and spine increase the puncture risk in this area. These injections are completed via an anterolateral approach.…”
Section: Introductionmentioning
confidence: 99%